2006
DOI: 10.1063/1.2354416
|View full text |Cite
|
Sign up to set email alerts
|

On the systematics of particle velocity histories in the shock-to-detonation transition regime

Abstract: Analysis of recent high quality, in-material gauge results from two cyclotetramethylene tetranitramine based explosives and one triamino trinitrobenzene based explosive has shown a number of significant correlations. These include the strong monotonic relationship between the local shock strength and the time to peak particle velocity along each particle path, and the simple scaling of velocity histories along the particle path that exists at a common local shock strength from shots with different initial cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…Point 1 suggested that each explosive particle was reacting independently of its neighbours, which led to the simple analytic model CIM [4]. The reactive burn model, CREST, followed from Point 3 and gained credibility from both it's success in predicting shock initiation and detonation phenomena and the Overall Conclusion of the analysis [3] that: "At least to first order, the reaction rate is solely dependent on two factors, shock strength and the time along a particle path since the shock passed. "…”
Section: Summary Of Evidencementioning
confidence: 99%
See 4 more Smart Citations
“…Point 1 suggested that each explosive particle was reacting independently of its neighbours, which led to the simple analytic model CIM [4]. The reactive burn model, CREST, followed from Point 3 and gained credibility from both it's success in predicting shock initiation and detonation phenomena and the Overall Conclusion of the analysis [3] that: "At least to first order, the reaction rate is solely dependent on two factors, shock strength and the time along a particle path since the shock passed. "…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Analysis of the experimental results [3,4] shows that: 1. The time of peak particle velocity initially moves away from the shock, then runs parallel (Δt ~ constant) to the shock, before it begins to accelerate like a normal hydrodynamic pulse, to catch up the shock.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 3 more Smart Citations